Man-Power for the Public Library System - Hithaishini, M. V. (Journal of Information and Knowledge, 1964)
Based on the data given in Papers P and Q of this issue,works out the man-power required for the public library system in India. Indicates the category and minimum staff required for one unit in each of the library systems. Shows that the total man-power required for the Librachines to be 106,190, that for the Branch Libraries to be 110,830, that for the City Central Libraries to be 4,017, that for the Rural Central Libraries to be 12,600, that for the State Central Libraries to be 4,880, and that for the National Central Library to be 1,231.